Enhanced mGlu5-receptor dependent long-term depression at the Schaffer collateral-CA1 synapse of congenitally learned helpless rats - Pignatelli, Marco; Vollmayr, Barbara; Richter, Sophie Helene; Middei, Silvia; Matrisciano, Francesco; Molinaro, Gemma; Nasca, Carla; Battaglia, Giuseppe; Ammassari-Teule, Martine; Feligioni, Marco; Nisticò, Robert; Nicoletti, Ferdinando; et al. (Neuropharmacology, 2013)
Alterations of the glutamatergic system have been implicated in the pathophysiology and treatment of major depression. In order to investigate the expression and function of mGlu5 receptors in an animal model for treatment-resistant depression we used rats bred for congenital learned helplessness (cLH) and the control strain, bred for resistance against inescapable stress, congenitally. not learned helpless rats (cNLH). Western blot analysis showed an increased expression of mGlu5 (but not mGlu1a) receptors in the hippocampus of cLH rats, as compared with control cNLH rats. We also examined mGlu1/5 receptor signaling by in vivo measurement of DHPG-stimulated polyphosphoinositides hydrolysis. Stimulation of 3H-inositolmonophosphate formation induced by i.c.v. injection of DHPG was enhanced by about 50% in the hippocampus of cLH rats. Correspondingly, DHPG-induced long-term depression (LTD) at Schaffer collateral/CA1 pyramidal cell synapses was amplified in hippocampal slices of cLH rats, whereas LTD induced by low frequency stimulation of the Schaffer collaterals did not change. Moreover, these effects were associated with decreased basal dendritic spine density of CA1 pyramidal cell in cLH rats. These data raise the attractive possibility that changes in the expression and function of mGlu5 receptors in the hippocampus might underlie the changes in synaptic plasticity associated with the depressive-like phenotype of cLH rats. However, chronic treatment of cLH rats with MPEP did not reverse learned helplessness, indicating that the enhanced mGlu5 receptor function is not the only player in the behavioral phenotype of this genetic model of depression. This article is part of a Special Issue entitled ‘Metabotropic Glutamate Receptors’.